Development of Guided Inquiry-Based Physics e-LKPD to Improve Students' Critical Thinking Abilities - Safitri, Riski; Jumadi, Jumadi; Simamora, Nadia Natalia (STKIP Singkawang, 2024)
The development of guided inquiry-based physics e-LKPD is based on the lack of learning media in the MAN 1 Yogyakarta physics subject that can help students think critically. The purpose of this research is to develop a proper, effective, and practical guided inquiry-based physics e-LKPD to help students improve their critical thinking ability. The method is the R&D 4D design model, including: define, design, develop, and disseminate. The data analysis technique used is quantitative. Quantitative data analysis is used to determine the level of feasibility, practicality, and effectiveness. The results showed that the guided inquiry-based physics e-LKPD that had been developed was feasible to apply with a percentage of 100% media experts, 89% material experts, and 100% language experts, and the e-LKPD was stated to be practical as seen from the achievement of teacher response sheets with an average of 100% and student response sheets with an average of 90.07%. The e-LKPD was also declared effective in terms of the post-test completeness achievement of 0.70 in the moderate category. Based on the results above, it can be concluded that the guided inquiry-based physics e-LKPD that has been developed is declared feasible, practical, and effective to use and can improve students' critical thinking ability.